Study on Structure and Physico-chemical Properties of Surficial Epoxidized Deproteinized Natural Rubber/silica blend - Nguyen, Thu Ha; Cao, Hong Ha; Nguyen, Pham Duy Linh; Phan, Trung Nghia (Old Journal, 2019)
The blends of epoxidized natural rubber/silica were prepared and characterized the properties which are necessary for the coating application. The epoxidized natural rubber was prepared by epoxidation of deproteinized natural rubber with fresh peracetic acid in latex stage. The blends of epoxidized natural rubber and silica were prepared from epoxidized natural rubber latex and tetraethyl orthosilicate. The structural characterization of products was carried out through latex state NMR and FT-IR spectroscopy and SEM observation. The contact angle of water drop on the surface of the blends and water uptake were investigated. The results from structural characterization showed that epoxy group was successfully introduced to natural rubber chain and silica particle was formed in epoxidized natural rubber matrix. The blend of epoxidized natural rubber containing 15 %mol of epoxy group content and 5 %w/w of tetraethyl orthosilicate was found to attain the highest hydrophobicity.